Estimation of the permafrost stability on the East Arctic shelf under the extreme climate warming scenario for the XXI century - V. V. Malakhova; E. N. Golubeva (Лëд и снег, 2016)
A state of permafrost in the Arctic is the key to understanding whether methane, stored in the permafrost related gas hydrate, can release into the atmosphere. The global warming can lead to destabilization of the submarine permafrost and, thus, cause the methane releasing into the water. The near-bottom water temperature plays a significant role in the current state of the submarine permafrost, because it specifies a depth of thawing of the permafrost. We have numerically simulated evolution of the submarine permafrost on the East Siberia Arctic shelf for the last glacial cycle. In order to estimate a possible state and stability of the submarine permafrost we did carry out a numerical run based on the ICMMG SB RAS the coupled ocean-ice and submarine permafrost model. For the atmosphere forcing, the GFDL CM3 coupled climate model output, simulated under the scenario RCP8.5, was used. The scenario RCP8.5 was used since it predicted the strongest warming by the end of the 21-st century. The GFDL СM3 model, predicting the most pronounced Arctic warming, was also used in order to put the tentative upper boundary on the submarine permafrost degradation in this century.The results obtained show that the offshore permafrost exists across the vast East Siberia shelf. This permafrost occurs continuously but its thickness changes. Thickness of the permafrost within the most part of the East Siberia shelf is estimated 470–590 m when the value of 60 W/m2 was used for the geothermal flux. Our results reveal a certain rising of the bottom layer temperature on the shelf and subsequent penetration of a heat flux into the sediments. However, our results show that even the extreme warming is not sufficient to destabilize the submarine permafrost on the shelf of both, the Laptev Sea and the East Siberian Sea. By the end of the 21st century, upper boundary of the permafrost deepens by value from 1 to 11 m only due to the thermal effects, and by 5–10 m in addition if we take into account the salinity of sediments. However, the depth of the permafrost upper boundary is still smaller than that of the hydrate stability zone. The thickness of the methane hydrate stability zone on the shelf is estimated 770–870 m. Moreover, upper boundary of this zone occurs at a depth of 120–220 m below the sea bottom, which makes the gas hydrates be isolated from the seabed surface by the permafrost layer. The submarine permafrost functions as an impermeable lid and prevents the methane from destroyed gas hydrates.